Investigating EFL Teachers’ Perceptions on the Implementation of Higher Order Thinking Skills in Semi-Urban Area - Puspitasari, Maya (Utamax : Journal of Ultimate Research and Trends in Education, 2025)
The implementation of Higher-Order Thinking Skills (HOTS) within Indonesia's Merdeka Curriculum has brought increasing attention to the development of critical and creative thinking across subjects. However, limited research has examined how English teachers, particularly in rural or semi-urban areas, perceive and apply HOTS-based assessment. This qualitative study addresses that gap by exploring the perceptions, confidence levels, and challenges experienced by junior secondary school English teachers when implementing HOTS. A two-day focus group discussion involving seven purposively selected teachers, followed by an open-ended questionnaire, served as the main data collection methods. Thematic analysis revealed that initial misconceptions linked HOTS to difficulty and content complexity. However, through collaborative discussions, participants gradually recognized HOTS as a pedagogical tool that fosters analytical, evaluative, and creative thinking in language learning. The study also found that teachers' confidence in designing HOTS-based assessments increased after the intervention, although they continued to face contextual barriers such as insufficient resources and limited student readiness. These findings indicate the need for continuous, context-sensitive professional development programs that not only enhance teacher understanding but also provide practical support. The study contributes to broader discussions on equitable curriculum reform by emphasizing the importance of empowering teachers in less advantaged regions. Its implications call for sustained investment in training strategies that ensure the effective integration of HOTS in English language education across diverse educational environments.